The girl : Marilyn Monroe, the seven year itch, and the birth of an unlikely feminist - Morgan, Michelle, 1970- (Running Press, 2018)
A look at how landing her role in "The Seven Year Itch," empowered Marilyn Monroe to embark on an adventure of self discovery, that transformed her from controlled wife to rebellious businesswoman and feminist.